The Effect of Compensation and Motivation on Employee Turnover at PT Indofood CBP Sukses Makmur Tbk - Widia Astuti (Jurnal Ekonomi dan Bisnis Digital, 2024)
The purpose of this study was to determine the significant effect of compensation and motivation on employee turnover at PT Indofood CBP Sukses Makmur Tbk. Snack Division either partially or simultaneously. This research was conducted at PT Indofood CBP Sukses Makmur Tbk. Snack Division having its address at Jalan Ancol Barat I No. 10, RW.3, Ancol, Kec. Pademangan, North Jakarta City, Special Capital Region of Jakarta 14430. The type of this research is quantitative with the method is causal research. The population in this study were employees of PT Indofood CBP Sukses Makmur Tbk. Snack Division consisted of 120 people and used a type of sample, namely the entire population was sampled, namely all employees of PT Indofood CBP Sukses Makmur Tbk. Snack Division has 120 employees. The results of this study note that compensation has a positive effect on employee turnover, this can be seen from the t test with tcount 9.134 > ttable 1.657 with a significance level of 0.000 this value is smaller than 0.1 (0.000 < 0.1). Motivation has a positive effect on Employee Turnover, this can be seen from the t-test with a t-value of 4.024 > t-table 1.657 with a significance level of 0.000 this value is greater than 0.1 (0.000 <0.1). Compensation and motivation have a positive and significant effect on employee turnover, this can be seen from the results of the F test with an Fcount of 43,333 while Ftable of 3.07 means 43,333> 3.07. Thus, it can be interpreted that discipline and motivation simultaneously have a significant influence on employee turnover.